Applicability of Propagation of Ultrasound Waves for Liquids and Glasses Materials (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The propagation of low-intensity ultrasound in polymers, acting as a high-frequency dynamic mechanical deformation, can be successfully used to monitor changes in the modulus of polymers associated with glass transition, crystallization, cross-linking, and other chemical and physical phenomena related to changes in the viscoelastic behavior, such as gelation phenomena. The velocity of sound is related to the polymer storage modulus and density, whereas the absorption of ultrasonic waves is related to the energy dissipation in the material and, therefore, to the loss modulus. Accordingly, ultrasonic measurements have been used by several authors to monitor the evolution of the viscoelastic moduli of polymers as a function of time or temperature and, recently, become a characterization technique of its own right, generally known as ultrasonic dynamic mechanical analysis (UDMA). Often the technique is used in conjunction with rheological methods as a means of providing a better insight into the viscoelastic behavior of polymer systems. As yet UDMA is underutilized primarily because of the low operating temperatures (usually below 100°C) of commercially available ultrasonic transducers, and also due to the requirement of a coupling medium to ensure an efficient energy transfer mechanism between the transducer and the test material. Despite these limitations, this paper shows that the use of ultrasonics is potentially a powerful method for the characterization of polymers, particularly as a tool for online monitoring of events occurring during polymer processing and in the manufacture of polymer matrix composites. The aim of this paper is to review the progress made in recent years, highlighting the potential and reliability of UDMA for monitoring physical transitions in polymers such as glass transition, melting, crystallization, as well as physical changes taking place during curing of thermosetting resins.